2001
DOI: 10.1074/jbc.m108374200
|View full text |Cite
|
Sign up to set email alerts
|

Alternatively Folded Choriogonadotropin Analogs

Abstract: Most heterodimeric proteins are stabilized by intersubunit contacts or disulfide bonds. In contrast, human chorionic gonadotropin (hCG) and other glycoprotein hormones are secured by a strand of their ␤-subunits that is wrapped around ␣-subunit loop 2 "like a seatbelt." During studies of hCG synthesis in COS-7 cells, we found that, when the seatbelt was prevented from forming the disulfide that normally "latches" it to the ␤-subunit, its carboxyl-terminal end can "scan" the surface of the heterodimer and becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 42 publications
(57 reference statements)
0
29
0
Order By: Relevance
“…Unlike the hCG heterodimer, which dissociated completely at pH 2 within 30 min at 37°C, only about 20% of the hCG/teFSH chimera heterodimer dissociated under these conditions. It was not as stable as heterodimers that contain an intersubunit disulfide, which do not dissociate under these conditions (13). These observations showed that we could distinguish heterodimers in which the seatbelt is latched to the ␣-subunit, heterodimers in which the seatbelt is latched to ␤Cys 5 , and heterodimers in which the seatbelt is latched to ␤Cys 26 by measuring differences in their stabilities at pH 2, 37°C.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…Unlike the hCG heterodimer, which dissociated completely at pH 2 within 30 min at 37°C, only about 20% of the hCG/teFSH chimera heterodimer dissociated under these conditions. It was not as stable as heterodimers that contain an intersubunit disulfide, which do not dissociate under these conditions (13). These observations showed that we could distinguish heterodimers in which the seatbelt is latched to the ␣-subunit, heterodimers in which the seatbelt is latched to ␤Cys 5 , and heterodimers in which the seatbelt is latched to ␤Cys 26 by measuring differences in their stabilities at pH 2, 37°C.…”
Section: Resultsmentioning
confidence: 69%
“…Previously, we had found that the hCG seatbelt in hCG␤-C26A is latched readily by a wraparound mechanism to either of these ␣-subunit analogs when it is prevented from latching with ␤Cys 26 (13). By analogy, we reasoned that if heterodimers containing the salmon seatbelt strap were latched by a wraparound mechanism, s/hCG␤-St,C26A would be latched readily to both ␣-S43C and ␣-S92C.…”
Section: Observation That Confirms Assembly Occurs By a Wraparoundmentioning
confidence: 99%
See 1 more Smart Citation
“…We have observed repeatedly that disulfide cross-linked hCG analogs are stable at pH 2, 37°C, for 30 min or longer; hCG and heterodimers that lack a disulfide cross-link under these conditions dissociate and become undetectable in heterodimerspecific assays (9,18). Therefore, before using cross-linked samples in binding or signal transduction assays, we routinely treated them at acid pH to destroy any heterodimers that lack a cross-link.…”
Section: Resultsmentioning
confidence: 99%
“…Materials secreted into the culture media were assayed by sandwich immunoassays (17) employing ␣-subunit antibody A113 for capture and radioiodinated ␤-subunit antibody B110 for detection. They were treated at acid pH to cause the dissociation of heterodimers that lack an intersubunit disulfide cross-link (18). Chinese hamster cells that overexpress the rat LHR were used to monitor the influence of the analogs on the ability of 125 I-hCG to bind LHR and to elicit cyclic AMP accumulation as reported previously (5,13,15).…”
Section: Methodsmentioning
confidence: 99%